Pemanfaatan Green Coke Sebagai Bahan Bakar Padat - Yulia, Indri; HS, Irdoni; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The need for alternative energy sources keep increasing, green coke is a byproduct from refenery unit that has a high heating value, so it is potential to be used as an alternative fuel. The purpose of this experiment was to study the green coke briquetting process, studied the effect of the pressing pressure against the produced briquettes, and determine the effect of operating conditions on the heating value and the resulting compressive strength. Green coke used in this experiment was tested fors carbon content, then do briquetting by adding starch with the composition ratio of green coke to starch (95:5, 90:10, and 85:15 %weight) and the variation of pressure (120, 150, 180 Kg/cm2), with response of heating value and compressive strength, the response data obtained were processed using Respone Surface Methodology (RSM) using Design Expert application. The pressing pressure and the ratio of green coke has a significant effect on the heating value and compressive strength. Highest heating value obtained in the comparison of green coke composition: adhesive 95: 5 and the pressing pressure of 180 kg / cm2 with a calorific value of 37685.4 Kj / Kg, and a compressive strength of 4.72 kg / cm2Keywords : alternative energy, compressive strength, heating value, starch.